The effectiveness of value style investing in South Africa - Langa, Senzo Innocent (My University, 2016)
Style investing is a well-documented global phenomenon that refers to the manner in which investors formulate their capital allocation decisions. The two broad styles of investing to be discussed in this report are the ‘value style’ and the ‘growth style’ investing. Recent empirical research suggests that value style of investing outperforms growth style investing over the long term. Rational theories suggest that a value premium exist because value counters have higher unsystematic risk. However, theories such as behavioural finance attribute the value premium to more psychological social factors such as emotional and heuristic biases. The aim of this study was to determine whether value style investing outperforms growth style investing in South Africa. For the purposes of this study, we evaluated the performance of various portfolios for the period of December 2000 to December 2015. In addition, the study determined the relative risk of the two styles, by testing whether value outperforms growth during periods of financial crisis, and during a period of slow economic growth. In defining the parameters of our study, we divided the constituents of Financial Times and London Stock Exchange/Johannesburg Stock Exchange (FTSE /JSE) index into growth and value based on their relative Price to book (P/B) going back to December 2000. This created four portfolios; namely, Deep value, Relative value, Relative growth and Super growth. Portfolio Analytics were employed to determine which style outperforms over the period. Regression analyses was used to ascertain which portfolio generated abnormal risk adjusted returns over the period. Relative risk is also analysed. The results of this research indicate that there is limited evidence of value premium in South Africa over the period of the study, albeit there are some periods where one style is dominant over the other. Regressions suggest that none of the portfolios constructed using market capital weighted generate abnormal returns. However, deep value, relative value and relative growth portfolios generate abnormal returns when constructed on equalweighted basis. On a relative risk basis, deep value outperforms during the financial crisis, whereas relative value outperforms during economic slowdowns.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in the field Finance and Investment Management) , 2016
Keywords: Investments--South Africa; Portfolio management--South Africa; Risk management--South Africa